2013
DOI: 10.12740/app/19959
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Attempted Suicide in Albanian Children's and Adolescents

Abstract: SummaryBackground. Attempted suicides and suicides are becoming pertinent social phenomena in Albania, with increasing trend in the last years, exceeding the road traffic accident numbers. Our objective was to examine suicide attempts trends among Albanian children and adolescents. Methods. We conducted a retrospective analysis of standardized suicide attempts rates in Statistic Department at University Hospital Center "Mother Theresa"; epidemiology data for the period spanning from 2006 to 2012. We analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In total, six school- and community-based (Aktepe, Çalişkan, & Sönmez, 2014; Kharsati & Bhola, 2015; Somer et al, 2015; Tang et al, 2011; Wan et al, 2011; Zoroglu et al, 2003) and nine hospital/clinic-based studies reported on the forms of self-harm (Akdemir, Zeki, Ünal, Kara, & Çetin, 2013; Akin & Berkem, 2012; Çelik et al, 2011; Fidan, Ceyhun, & Kirpinar, 2009; Fidan & Kirpinar, 2009; Gökçen & Köylü, 2011; Grover, Sarkar, Chakrabarti, Malhotra, & Avasthi, 2015; Kola, Kola, Petrela, & Zaimi, 2013; Soylu, Taneli, & Taneli, 2013; Syed & Khan, 2008). Banging and hitting were the most common form of self-harm in the community-based studies, followed by cutting, scratching and wound picking (Aktepe et al, 2014; Kharsati & Bhola, 2015; Somer et al, 2015; Tang et al, 2011; Wan et al, 2011; Zoroglu et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, six school- and community-based (Aktepe, Çalişkan, & Sönmez, 2014; Kharsati & Bhola, 2015; Somer et al, 2015; Tang et al, 2011; Wan et al, 2011; Zoroglu et al, 2003) and nine hospital/clinic-based studies reported on the forms of self-harm (Akdemir, Zeki, Ünal, Kara, & Çetin, 2013; Akin & Berkem, 2012; Çelik et al, 2011; Fidan, Ceyhun, & Kirpinar, 2009; Fidan & Kirpinar, 2009; Gökçen & Köylü, 2011; Grover, Sarkar, Chakrabarti, Malhotra, & Avasthi, 2015; Kola, Kola, Petrela, & Zaimi, 2013; Soylu, Taneli, & Taneli, 2013; Syed & Khan, 2008). Banging and hitting were the most common form of self-harm in the community-based studies, followed by cutting, scratching and wound picking (Aktepe et al, 2014; Kharsati & Bhola, 2015; Somer et al, 2015; Tang et al, 2011; Wan et al, 2011; Zoroglu et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Burning and use of chemicals were the least common forms of self-harm (Wan et al, 2011; Zoroglu et al, 2003). In the hospital-based studies, self-poisoning was the commonest method (Akin & Berkem, 2012; Çelik et al, 2011; Fidan et al, 2009; Fidan & Kirpinar, 2009; Gökçen & Köylü, 2011; Grover et al, 2015; Kola et al, 2013; Soylu et al, 2013; Syed & Khan, 2008). Pesticides were a common choice of poisoning (Grover et al, 2015; Kola et al, 2013; Syed & Khan, 2008; Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent publications have raised concerns regarding a constant increasing trend of suicide rates in Albania, with self-poisoning being a method of choice [ 4 ]. The same seems to be valid for attempted suicides, with more than 97% of adolescents trying to self-poison themselves with pharmaceuticals [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The suicide attempts are actions with suicidal aim, not resulting in death [14]. In our study we've analyzed suicide attempts among inpatients at the Clinic of Neurology and Psychiatry for Children and Youth in Belgrade.…”
Section: Discussionmentioning
confidence: 99%
“…Drug overdose was found to be the most common mode for suicide attempt (66.2%), followed by wrist cutting (11.5%), and hanging (10.8%). In the other studies, drug poisoning is also reported as the most common method of suicide attempt [14,15]. Possibly, one of the reason is that drugs can be easily procured and available in home inventories.…”
Section: Discussionmentioning
confidence: 99%